2021
DOI: 10.1155/2021/9124656
|View full text |Cite
|
Sign up to set email alerts
|

Increased Arterial Stiffness as a Predictor for Onset and Progression of Diabetic Retinopathy in Type 2 Diabetes Mellitus

Abstract: Introduction. Brachial–ankle pulse wave velocity (baPWV), an indicator of arterial stiffness, has been demonstrated to be associated with type 2 diabetes mellitus (T2DM) and its vascular complications. This study was aimed at investigating the correlations of baPWV with both the presence and severity of diabetic retinopathy (DR) at baseline and at exploring the predictive role of baPWV in the new onset/progression of DR in the follow-up analysis. Methods. The prospective cohort study recruited 2,473 Chinese pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Increases in large elastic artery stiffness (i.e., increased aortic PWV and intrinsic mechanical wall stiffness) with aging is a major independent predictor of age‐associated clinical CVD (Vasan et al., 2022 ), impaired glucose tolerance (Zheng et al., 2023 ), kidney dysfunction (Ford et al., 2010 ), cognitive impairment (Thorin‐Trescases et al., 2018 ), and diabetic retinopathy (An et al., 2021 ). Fisetin supplementation reduced arterial stiffness (aortic PWV) in old wild‐type mice by reducing aortic intrinsic mechanical wall stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…Increases in large elastic artery stiffness (i.e., increased aortic PWV and intrinsic mechanical wall stiffness) with aging is a major independent predictor of age‐associated clinical CVD (Vasan et al., 2022 ), impaired glucose tolerance (Zheng et al., 2023 ), kidney dysfunction (Ford et al., 2010 ), cognitive impairment (Thorin‐Trescases et al., 2018 ), and diabetic retinopathy (An et al., 2021 ). Fisetin supplementation reduced arterial stiffness (aortic PWV) in old wild‐type mice by reducing aortic intrinsic mechanical wall stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, reviews suggest that the most significant risk factors for the initiation and progression of DR include smoking, a high body mass index, insufficient glycemic control, hypertension, a long history of diabetes, dyslipidemia, and microalbuminuria ( 24 , 25 ). Arterial stiffness has also been proposed as a risk factor related to DR in recent years ( 26 ). Although the exact role of these factors in the pathogenesis of DR is not well-defined, they are important in guiding DR screening and the development of public healthcare strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a positive association of baPWV with the T2DM retinopathy group was found. A previous study reported that higher baPWV values are associated with the presence and severity of DR, and baseline baPWV may be an independent predictor in new-onset DR.[ 5 ] Liu Sung-Chen et al (2020) reported that ‘high baPWV is strongly associated with risk of severe DR, especially PDR’. [ 15 ] It can be inferred from the present study that increased systemic arterial stiffness is present in diabetic retinopathy patients and as systemic vascular stiffness increases, the chance of the existence of diabetic retinopathy also increases.…”
Section: Discussionmentioning
confidence: 99%
“…Arterial stiffness may decrease intra-arterial wave reflection and increase pulsatile pressure, which may cause damage to retinal microcirculation. [ 4 ] Several studies tried to understand the association of arterial stiffness and endothelial dysfunction with DR or the severity of DR.[ 5 6 7 ] But there is no conclusive answer to it. Moreover, the prevalence of cardiac autonomic neuropathy (CAN) at the time of diagnosis of T2DM is around 7%, and it increases with the duration of diabetes by 4.6– 6% per year.…”
Section: Introductionmentioning
confidence: 99%